Developing Barcorious Application as Teaching Media for English Young Students: Focus on Implication - Ahmad, Arimuliani (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2018)
Recently, teaching English for young learners especially for elementary school level still becomes problem in practice especially in Pekanbaru. Practically, the teachers teach their students without standard guidance to go with such as curriculum and syllabus because for fourth grades students, English Language subject looks like as extra subject which affects the effort to teach maximal. As response to this issue, the researcher has developed a learning media which focuses on vocabulary mastery which provides chance for the students to learn with or without teacher. There are five stages in developing this media which called by Barcorious such as analyzing students’ need, designing media, developing content and design, implementation media, and evaluation. This study describes the implementation of Barcorious application to enhance students’ vocabulary mastery. Indeed, this media was implemented for teaching four grade students. There was one class which consisted of 35 students participated. The finding shows this media can give significant improvement of students’ vocabulary mastery because the students’ post-test higher than pre-test.